PANDANGAN POSTMILENIALISME DAN SUMBANGSIHNYA BAGI PEMULIHAN KONDISI MENTAL ORANG KRISTEN PADA MASA PASCA PANDEMI COVID-19 - Theodorus Miraji; Felicia Irawaty (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2021)
2020 is a tough year for humans due to the Covid-19 pandemic which has attacked all sides of human life. One of the most affected is the human mentality, and this mentality must be restored so that in the post-pandemic era, humans can be active and do everything as before. The church also has a duty to carry out this and the church has teachings that can be given to humans in general and Christians in particular as material for healing, one of which is eschatology which relates to the teachings of Postmillennialism. The method of this research is descriptive method with literature study techniques. Some of the characteristics of Postmillennial teachings are: First, Postmillennialists believe that what mankind is waiting for, namely the coming of God's reign, has actually started since the first coming of Jesus. Second, the 1000 year reign is led by Jesus through the church and Third, Postmillennialism believes in the central role of the gospel. From these characteristics, the Postmillennial Viewpoint can contribute to raising hope for the future and as material for Christian Counseling / Pastoral Assistance, contributing to encouraging churches to be actively involved in human life, Postmillennialism Views Encourage evangelism as a human need in the post-pandemic era